Vocabulary variety of Japanese in tourism field - Ni Wayan Meidariani; Ni Luh Gede Meilantari (English, 2018)
The growing number of Japanese tourists to Bali has resulted in large numbers of workers in the tourism sector, such as Japanese language tour guide, GRO and hotel staff, Japanese travel agency staff and others. To provide good service to Japanese tourists, the quality of tourism practitioners also need to be improved both from the attitude, hospitality, security and the ability to speak Japanese so that Japanese tourists feel comfortable while on the island of Bali. Efforts to improve the ability of Japanese language, the vocabulary knowledge of tour guide is needed to be able to use the vocabulary in context. Based on the phenomenon, then this paper discusses the variety of Japanese vocabulary that is often used when doing tourism activities in some tourist attractions in Gianyar regency. The problems discussed in this paper is what kind of tourist vocabulary is commonly spoken Japanese tourists when visiting the tourist attraction on the island of Bali. In general, this study aims to support the program of Welcome to Bali in order to become more popular bali tourism that can increase the number of Japanese tourists to come to visit the island of Bali. The specific purpose of this research is to (1) know the Japanese language vocabulary of tourism spoken by Japanese tourists so that the vocabulary can be used as a reference for tourism practitioners in order to increase the knowledge of Japanese language vocabulary of tourism. The approach used in this study is a qualitative approach. Research approach by processing the data source that is descriptive by using descriptive method qualitatif. The research was done in tourist object in Ubud area. The data types are primary data with lingual data sources obtained from Japanese tourist communications. The observations show that the vocabulary spoken by Japanese tourists is a vocabulary that is related to cultural and natural activities such as esute, chiketto, raisu terasu, kojin takushi, mise, subarashii. Japanese tourists often use joshi as a complement to a speech to tourism practitioners in communicating. Joshi also sometimes omitted in speech but still acceptable.